Method for degrading polystyrene plastic and upgrading and recycling polystyrene plastic into benzoic acid based on nano MnO2 photocatalysis ozonation

By using the synergistic effect of nano-MnO2 photocatalyst and ozone, the problems of low interfacial contact efficiency and catalyst photocorrosion in the nano-MnO2 photocatalytic ozone degradation of polystyrene were solved, achieving efficient generation of benzoic acid under mild conditions and improving resource utilization efficiency.

CN121342644APending Publication Date: 2026-01-16GUANGDONG UNIV OF PETROCHEMICAL TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511578398.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing nano-MnO2 photocatalytic ozone degradation technology for polystyrene suffers from problems such as low interfacial contact efficiency, limited reaction rate, complex degradation pathway, catalyst photocorrosion, and low ozone utilization, making it difficult to achieve highly selective synthesis of benzoic acid under mild conditions.

Method used

By employing the synergistic effect of nano-MnO2 photocatalyst and ozone, benzoic acid is generated through an oxidative degradation reaction under normal pressure via light irradiation. The reaction conditions are mild and energy consumption is low. Photogenerated electron-hole pairs are used to promote the decomposition of ozone into highly active free radicals. The reaction parameters are optimized to improve carrier separation efficiency and ozone activation capability.

Benefits of technology

The efficient and directional conversion of polystyrene to benzoic acid was achieved with a yield of over 60%. The reaction process is environmentally friendly, conforms to the principles of green chemistry, and has high degradation efficiency and low energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a method for degrading polystyrene (PS) plastic and upgrading and recycling the PS plastic into benzoic acid based on nano MnO2 photocatalytic ozonation, and belongs to the technical field of solid waste recycling. The method comprises the following steps: firstly, mixing PS plastic fragments with nano MnO2 and an organic solvent, then simultaneously introducing ozone into a reaction system at normal temperature and normal pressure, and irradiating with light. Through synergistic catalysis of light and ozone, molecular chains of the PS plastic can be efficiently and selectively broken and oxidized, and finally the PS plastic is directionally converted into benzoic acid with high additional value. After the reaction is finished, a benzoic acid product can be obtained through simple separation, concentration and purification steps. The method provided by the invention realizes high-valued recycling of the waste PS plastic under mild conditions, solves the problems of high energy consumption, complex products, easy generation of secondary pollution and the like in a traditional treatment method, and has the outstanding advantages of green process, efficient reaction, high product value and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid waste resource utilization technology, specifically relating to a method for degrading polystyrene plastic based on nano-MnO2 photocatalytic ozone oxidation and recycling it into benzoic acid. Background Technology

[0002] Plastic pollution has become a global environmental challenge. Polystyrene (PS), as one of the most widely produced general-purpose plastics, is difficult to degrade in the natural environment due to its stable benzene ring structure and hydrophobic properties, leading to its persistent accumulation in soil and oceans and posing serious ecological risks. Traditional polystyrene waste treatment mainly relies on landfill and incineration. The former consumes land resources and may lead to microplastic leaching, while the latter may produce toxic gases such as dioxins due to incomplete combustion and directly emit large amounts of the greenhouse gas carbon dioxide, neither of which conforms to the concept of a green circular economy. Therefore, developing efficient and clean polystyrene degradation and resource utilization technologies to achieve high-value transformation of waste has become an important research direction in the fields of environmental engineering and green chemistry.

[0003] Among existing polystyrene treatment technologies, biodegradation is difficult to apply practically due to the low metabolic rate of microorganisms and their limited effect on polymer chains. While pyrolysis can produce liquid fuels, it typically requires high temperatures (>400°C) and produces complex products with high separation and purification costs. Advanced oxidation technologies (AOPs) have shown potential in treating recalcitrant organic compounds due to their strong oxidizing capabilities. Ozone oxidation, in particular, achieves C–C bond cleavage through direct attack of ozone molecules or the generation of ·OH radicals. However, ozone alone has low selective ring-opening efficiency for aromatic rings in polystyrene and is prone to incomplete oxidation due to mass transfer limitations.

[0004] The coupling of nano-MnO2 photocatalysis with ozone oxidation offers a novel approach to addressing these issues. Nano-MnO2 photocatalysts (such as semiconductor materials like TiO2 and ZnO) generate photogenerated electron-hole pairs under UV or visible light excitation, promoting ozone decomposition into more reactive free radical species such as ·O2⁻ and ·OH, forming a synergistic oxidation system. This system not only accelerates the chain breakage of polystyrene macromolecules but also regulates the distribution of intermediate products through free radical pathways, preventing excessive mineralization into CO2. However, existing nano-MnO2 photocatalytic ozone degradation technology for polystyrene still faces several key scientific problems and technological bottlenecks: First, the hydrophobicity and solid-state nature of polystyrene result in low interfacial contact efficiency with nano-MnO2 photocatalysts and ozone, limiting the reaction rate to multiphase mass transfer processes; second, the degradation pathway is complex, with intermediate products such as acetophenone and benzaldehyde easily further oxidized and ring-opened, leading to insufficient selectivity for the target product benzoic acid; furthermore, issues such as catalyst photocorrosion and low ozone utilization also restrict the large-scale application of this technology. To address these challenges, researchers have recently focused on developing novel composite nano-MnO2 photocatalytic materials to improve carrier separation efficiency and ozone activation capabilities; optimizing reaction media to improve mass transfer conditions in polystyrene; and enhancing multiphase interactions between light, ozone, catalyst, and substrate through reactor design. These explorations provide a theoretical basis for the photocatalytic ozone degradation and resource recovery of polystyrene using nano-MnO2. However, achieving highly selective synthesis of benzoic acid under mild conditions still requires in-depth research into reaction mechanisms, pathway control, and system integration.

[0005] In summary, this invention develops a highly efficient and green technology for the photocatalytic ozone oxidation degradation of polystyrene and the upgraded recovery of benzoic acid based on nano-MnO2. This not only helps solve the problem of white pollution but also aligns with the sustainable development goal of "waste resource utilization." By optimizing the design of the nano-MnO2 photocatalyst, controlling reaction parameters, and elucidating the free radical mechanism, the directional conversion of polystyrene to benzoic acid is achieved. Benzoic acid, as an important chemical intermediate, is widely used in the pharmaceutical, dye, and food industries. Its directional synthesis from waste materials offers both environmental benefits and economic value, providing an innovative technological path for the circular economy of plastics. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for degrading polystyrene plastics and upgrading and recycling them into benzoic acid based on nano-MnO2 photocatalytic ozone oxidation. This method has mild reaction conditions, low energy consumption, high degradation efficiency, and can achieve targeted upgrading and recycling of PS plastics into benzoic acid.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for degrading polystyrene plastic and recycling it to benzoic acid based on photocatalytic ozone oxidation using nano-MnO2 includes the following steps: a) Mix polystyrene plastic, nano-MnO2, and an organic solvent to form a reaction system; b) Under normal pressure and 10~50℃ conditions, a mixture of oxygen gas containing ozone and ozone is simultaneously introduced into the reaction system and subjected to light irradiation to cause an oxidative degradation reaction, generating a solution containing benzoic acid. c) Separate and purify the solution obtained in step b) to obtain the benzoic acid product.

[0008] Further, in step a), the organic solvent is one or more of acetonitrile, ethyl acetate, tetrahydrofuran, dichloromethane, and acetone, with acetic acid as an additive. The waste PS plastic products need to be cleaned, dried, and crushed into fragments or particles with a particle size of less than 10 mm.

[0009] Further, in step a), the amount of nano-MnO2 added is 2.5-15% of the molar amount of the repeating unit in the polystyrene plastic, and the amount of acetic acid added is 3-8% of the molar amount of the repeating unit in the polystyrene plastic; the mass-volume ratio of styrene plastic to organic solvent is 1g : (30-200) mL.

[0010] Further, in step b), the ozone-containing mixed gas refers to the gas produced by an ozone generator using air as the gas source, and it was found that the air intake of the ozone generator is 0.1~1.0 L / min.

[0011] Further, in step b), the wavelength range of the light is 256~490 nm. Preferably, the wavelength of the light is 450 nm.

[0012] Furthermore, in step b), the light is provided by an ultraviolet lamp with a power of 10~200 W.

[0013] Furthermore, in step b), the oxidative degradation reaction takes 1 to 48 hours.

[0014] Further, in step b), the reaction temperature is 20~50 ℃. Preferably, the reaction temperature is 25~40 ℃.

[0015] Further, in step c), the separation and purification includes: first filtering to remove solid residue, then adjusting the pH to 3-4 with acid, removing the solvent by vacuum distillation, and finally obtaining purified benzoic acid by recrystallization or column chromatography.

[0016] The beneficial effects of this invention are as follows: Mild conditions and low energy consumption: This invention is carried out at normal temperature and pressure, and utilizes the synergistic effect of light and ozone to avoid the high temperature and high pressure conditions of traditional pyrolysis / pyrolysis methods, which significantly reduces energy consumption and equipment requirements.

[0017] Efficient degradation and targeted conversion: Photocatalyzed ozone decomposition generates hydroxyl radicals (·OH) with stronger oxidizing power. These reactive species can efficiently attack the benzene ring and carbon chain of PS molecules, selectively converting the main structural units of PS into benzoic acid through a series of oxidation reactions, rather than a complex mixture. The yield of benzoic acid can reach over 60% (based on styrene units in PS).

[0018] High degree of resource utilization: Waste PS plastic is directly converted into benzoic acid, which has a wide range of applications (such as food preservatives, pharmaceutical intermediates, and chemical raw materials), realizing the upgraded recycling of "turning waste into treasure" and improving the economic efficiency of the recycling process.

[0019] Environmentally friendly: The entire reaction process does not produce toxic or harmful gases, and the solvent can be recycled, which is in line with the principles of green chemistry. Attached Figure Description

[0020] Figure 1 The 1H NMR spectrum of the benzoic acid product obtained in the examples; Figure 2 The carbon NMR spectrum of the benzoic acid product obtained in the examples; Figure 3 This is a process flow diagram of the method described in this invention; Figure 4 A schematic diagram of the mechanism of photocatalytic ozone oxidation degradation of polystyrene. Detailed Implementation

[0021] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0022] δ-nano manganese dioxide was prepared according to the literature method (Zhang, D., Dai, J., Zhang, J., Zhang, Y., Liu, H., Xu, Y., ...&Li, P. Preparation of Spherical δ-MnO2 Nanoflowers by One-Step Coprecipitation Method as Electrode Material for Supercapacitor. Acs Omega, 2024, 9(16), 18032-18045.). Spherical δ-MnO2 nanosheets were synthesized via a simple chemical coprecipitation method, as follows: KMnO4 (2.016 g), MnSO4·H2O (0.654 g), and deionized water (100 mL) were added to a three-necked flask, and the mixture was mechanically stirred continuously for 1 hour. Then, 2.5 mL of concentrated sulfuric acid was slowly added, and stirring continued for 1 hour. The mixture was then heated in an 80°C water bath and stirred vigorously for 1 hour until complete. The reaction solution was filtered and washed with deionized water until the pH of the filtrate was 7. The filter cake was dried in an oven at 80 °C for 24 hours. The resulting product was named δ-nano manganese dioxide.

[0023] Example 1 A method for degrading polystyrene plastics and recycling them into benzoic acid based on photocatalytic ozone oxidation using nano-MnO2, such as... Figure 1 As shown, it includes the following steps: Take 10 g (0.1 mol per repeating unit) of waste PS foam, wash and dry it, and then cut it into pieces approximately 5 mm in size. Place the treated PS fragments and 870 mg (0.01 mol) of δ-nano manganese dioxide into a 500 mL quartz reactor. Add 0.005 mol acetic acid and 1000 mL acetonitrile as solvents, and stir to ensure thorough wetting. Turn on an ozone generator (10 g, 220 V, quartz tube intelligent circulation control), and observe an air intake rate of 0.5 L / min, continuously introducing ozone into the reaction solution. Simultaneously, turn on a 450 nm wavelength, 30 W ultraviolet lamp to irradiate the reaction system. The reaction is carried out at room temperature (approximately 25 °C) and atmospheric pressure for 36 hours. After the reaction, the PS solids are almost completely eliminated, and the solution turns pale yellow. Filter the reaction solution, then acidify the pH to 3 with hydrochloric acid. Perform vacuum distillation on the filtrate to recover most of the acetonitrile solvent. The remaining concentrate was dissolved in a small amount of hot water at 75°C. After cooling, white crystals precipitated. After filtration and drying in an oven at 60°C, 7.9 g of white needle-like crystals were obtained. TLC and NMR analysis identified the product as benzoic acid with a purity greater than 98%. The calculated yield of benzoic acid was approximately 65% ​​(based on the theoretical molar amount of styrene units in the added PS). The 1H and 1C NMR spectra are shown below. Figure 1 and Figure 2 As shown, 1 H NMR (400 MHz, DMSO- d 6) δ 12.97 (s, 1 H, -COOH), 7.94 (d, J= 7.4 Hz, 2 H, Ar-H), 7.62 (t, J = 7.1 Hz, 1 H, Ar-H), 7.50 (t, J = 7.4 Hz, 2H, Ar-H). 13 C NMR (101 MHz, DMSO- d 6) δ167.4, 132.9, 130.8, 129.3, 128.6. Example 2 5 g of PS plastic fragments (approximately 2 mm in diameter) and 220 mg of δ-nano manganese dioxide were placed in a 250 mL reaction flask, along with 0.0025 mol of acetic acid and 500 mL of tetrahydrofuran. Ozone-containing air was introduced into the reaction system through an ozone generator at a flow rate of 0.2 L / min, while the system was simultaneously irradiated with a 365 nm / 254 nm dual-wavelength UV lamp (total power 50 W). The reaction was carried out in a 30 °C water bath for 18 hours. Post-reaction treatment was the same as in Example 1, yielding 3.78 g of benzoic acid, with a yield of approximately 62%.

[0024] Example 3 10 g of PS plastic granules (100 mesh) and 440 mg of δ-nano manganese dioxide were placed in a 1000 mL reactor, along with 0.005 mol of acetic acid and 1000 mL of acetone. Ozone-containing air was introduced into the reaction system through an ozone generator at a flow rate of 1.0 L / min, while the system was simultaneously irradiated with a 390 nm UV lamp (15 W). The reaction was carried out at 40 °C for 48 hours. Post-reaction treatment was the same as in Example 1, yielding 7.1 g of benzoic acid, with a yield of approximately 58%.

[0025] Comparative Example 1 The operating procedure was exactly the same as in Example 1, but the light source was not turned on, and the reaction was carried out for 6 hours under ozone alone. The results showed that the PS plastic only partially dissolved, the solution was turbid, and there were a large amount of white flocculent or powdery suspended matter. The yield of benzoic acid after treatment was extremely low, less than 5%. This indicates that without δ-nano MnO2 photocatalysis, ozone oxidation alone is insufficient to achieve efficient degradation of PS and selective formation of benzoic acid.

[0026] Comparative Example 2 The operating procedure was exactly the same as in Example 1, but ozone was not introduced; the reaction was carried out under light irradiation for 6 hours. The results showed that the PS plastic swelled slightly in the solvent, but there were no obvious signs of degradation, and no benzoic acid was detected.

[0027] Comparative Example 3 Take 0.625 mmol of PS fragments (200 mesh), 0.0625 mmol of catalyst (or no catalyst added), and place them in a 10 mL reactor. Add 0.03125 mmol of acetic acid and 6 mL of ethyl acetate. Purge the reaction system with ozone (air flow rate 3.0 L / min) while simultaneously irradiating with a 450 nm UV lamp. The reaction is carried out at 25 °C for 8 hours. Post-reaction treatment is the same as in Example 1, and the yield of benzoic acid is calculated. The results are shown in Table 1.

[0028] surface Different catalysts Note: 0.625 mmol PS, 10 mol% catalyst, 8 h, rt, 450 nm, 5 mol% acetic acid, 6 mL EtOAc, O3. Table 1 shows that the reaction is significantly improved with the use of a catalyst. While the reaction can proceed to some extent without a catalyst, achieving plastic degradation, the efficiency is relatively low. Furthermore, different catalysts have significantly different effects on the yield, indicating that the addition of δ-nano manganese dioxide catalyst plays a crucial role in enhancing the degradation rate and obtaining the high-value chemical benzoic acid.

[0029] Comparative Example 4 The operation steps were exactly the same as those in Comparative Example 3. Using δ-nano MnO2 as a catalyst, the reaction system was irradiated with wavelengths of 450 nm or 390 nm under the same reaction time (8 hours) and other conditions as before, and the yield of benzoic acid was calculated. The results are shown in Table 1.

[0030] Table 2. UV-Vis light sources of different wavelengths Note: 0.625 mmol PS, 10 mol% δ-nano MnO2, 8 h, rt, 390 / 450 nm, 5 mol% acetic acid, 6 mL EtOAc, O3. As shown in Table 2, compared to the 390nm light wavelength, 450nm is the optimal wavelength for maximizing the catalytic activity of δ-nano MnO2 catalysts.

[0031] Comparative Example 5 The operation steps were exactly the same as those in Comparative Example 3. δ-nano MnO2 was used as the catalyst, and the oxidative degradation experiment was carried out by only changing the reaction time. The yield of benzoic acid was calculated, and the results are shown in Table 3.

[0032] surface reaction time Note: 0.625 mmol PS, 10 mol% δ-nano MnO2, xh, rt, 450 nm, 5 mol% acetic acid, 6 mL EtOAc, O3. As shown in Table 3, the reaction effect is best when the reaction time is controlled at 8 hours. The yield of 10 hours (37.5%) is lower than that of 8 hours (58.7%). This may be because the ozone concentration is too high, which causes the free radical balance to be broken. For example, the peroxide free radicals that play an important role in the degradation of polystyrene plastics are consumed, which may lead to the accumulation of intermediate products, which are more difficult to be further oxidized and decomposed, making it difficult for the entire degradation process to proceed smoothly.

[0033] Comparative Example 6 The operation steps were exactly the same as those in Comparative Example 3. δ-nano MnO2 was used as the catalyst, and only the air intake of the ozone generator was changed. The yield of benzoic acid was calculated, and the results are shown in Table 4.

[0034] Table 4. Air intake volume (LPM) of ozone generator Note: 0.625 mmol PS, 10 mol% δ-nano MnO2, 8 h, rt, 450 nm, 5 mol% acetic acid, 6 mL EtOAc, O3. Table 4 shows that, at a light source wavelength of 450 nm and a reaction time controlled at 8 hours, within a certain range, as the air intake increases, more oxygen molecules enter the ozone generator, resulting in a higher ozone flow rate and concentration. Simultaneously, an appropriate airflow velocity can prevent excessive ozone decomposition due to localized high temperatures, thus maintaining a uniform ozone flow rate and ensuring smooth reaction. In the single-factor control experiment of the ozone generator's air intake velocity, it was found that maintaining an air intake velocity of 3 L / min resulted in the best reaction effect.

[0035] The mechanism diagram of photocatalytic ozone oxidation degradation of polystyrene is shown below. Figure 4 As shown, the possible mechanism for the degradation of polystyrene plastic using δ-nano manganese dioxide as a catalyst is as follows: Under irradiation with visible light at a specific wavelength of 450 nm, the manganese dioxide catalyst is excited by light energy and generates photogenerated electrons (electrons). ⁻ ) and photogenerated holes (h ⁺ With the help of δ-nano manganese dioxide surface active sites, ozone molecules (O3) gain electrons and are converted into oxygen (O2) and peroxide free radicals (such as ·O2). - O2 2- Reactive oxygen species, such as manganese dioxide, possess strong oxidizing power and can attack the CH bonds on the polystyrene (PS) molecular chain. Through a hydrogen atom transfer (HAT) mechanism, they abstract hydrogen atoms to generate benzyl radicals (Ph-CH2·). These benzyl radicals (Ph-CH2·) are unstable and further react with reactive oxygen species in the system to form benzene peroxide radicals (Ph-CH2-OO·). Subsequently, the benzene peroxide radicals initiate a series of β-cleavage reactions, producing relatively small molecular weight intermediates, such as benzaldehyde (Ph-CHO). These intermediates are further oxidized by reactive oxygen species in the system, ultimately yielding benzoic acid (Ph-COOH). During the reaction, manganese dioxide participates in the reaction and can be recycled back to its initial state, achieving catalyst recovery and ensuring the continuous cyclical degradation of polystyrene by photocatalytic ozone oxidation.

[0036] The above embodiments and comparative examples demonstrate that the synergistic effect of light and ozone is the key to achieving the technical effect of this invention.

Claims

1. A method for degrading polystyrene plastic by nano-MnO2-based photocatalytic ozone oxidation and upgrading and recycling to benzoic acid, characterized in that, The method comprises the following steps: a) mixing polystyrene plastic, nano-MnO2, acetic acid and an organic solvent to form a reaction system; b) under normal pressure and at 10-50 DEG C, simultaneously introducing a mixed gas containing ozone into the reaction system and performing light irradiation, so that an oxidative degradation reaction occurs to generate a solution containing benzoic acid; c) separating and purifying the solution obtained in step b) to obtain a benzoic acid product.

2. The method of claim 1, wherein, In step a), the organic solvent is one or more of acetonitrile, ethyl acetate, tetrahydrofuran, dichloromethane and acetone.

3. The method of claim 1, wherein, In step a), the addition amount of nano-MnO2 is 2.5-15% of the molar amount of the repeating units in the polystyrene plastic, and the addition amount of acetic acid is 3-8% of the molar amount of the repeating units in the polystyrene plastic.

4. The method of claim 1, wherein, In step b), the mixed gas containing ozone is obtained by using an ozone generator with air as the gas source, and it is found that the air inlet amount of the ozone generator is 0.1-1.0 L / min.

5. The method of claim 1, wherein, In step b), the wavelength range of the light is 256-490 nm.

6. The method of claim 5, wherein, The wavelength of the light is 450 nm.

7. The method of claim 1, wherein, In step b), the light is provided by an ultraviolet lamp with a power of 25-200 W.

8. The method of claim 1, wherein, In step b), the time of the oxidative degradation reaction is 1-48 hours.

9. The method of claim 1, wherein, In step b), the reaction temperature is 20-50 DEG C.

10. The method of claim 1, wherein, In step c), the separation and purification comprises: first removing solid residues by filtration, then adjusting the pH to 3-4 with an acid, removing the solvent by reduced pressure distillation, and finally obtaining the purified benzoic acid through recrystallization or column chromatography.

Citation Information

Cited By

  • Method for producing benzoic acid by degrading polystyrene through photo-thermal synergistic catalyst and application of method

    CN121990900A

  • Method for degrading polystyrene to produce benzoic acid by using a photo-thermal synergistic catalyst and application thereof

    CN121990900B